2012
DOI: 10.1136/sextrans-2012-050580
|View full text |Cite
|
Sign up to set email alerts
|

Risk of HIV or second syphilis infection in Danish men with newly acquired syphilis in the period 2000–2010

Abstract: ObjectivesRisk of subsequent diagnosis of HIV in persons diagnosed with newly acquired syphilis, and syphilis in HIV-infected persons, are of interest as these infections are markers of unsafe sex.MethodsFrom a nationwide register, all Danish men aged >16 years diagnosed with syphilis in the period 2000–2010 (n=1217) were identified, and subsequently data on HIV status was extracted from the Danish HIV Cohort Study. We used Kaplan–Meier analysis to estimate the 5-year risk of HIV and second syphilis infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
1
21
0
2
Order By: Relevance
“…The same applies to the study of Centers for Disease Control and Prevention 15 and Taylor et al 32 Some researchers suggest the immediate initiation of ART in seropositive MSM with syphilis coinfection and high VL, in order to reduce the chances of HIV transmission. 33 Genotypic testing of samples from the five patients receiving ART and who experienced increased VL after syphilis treatment in this study revealed development of viral mutations that conferred resistance to antiretroviral drugs. Those five patients who developed resistance were compliant to the treatment and they never had identifiable VL previous to syphilis infection.…”
Section: Discussionmentioning
confidence: 96%
“…The same applies to the study of Centers for Disease Control and Prevention 15 and Taylor et al 32 Some researchers suggest the immediate initiation of ART in seropositive MSM with syphilis coinfection and high VL, in order to reduce the chances of HIV transmission. 33 Genotypic testing of samples from the five patients receiving ART and who experienced increased VL after syphilis treatment in this study revealed development of viral mutations that conferred resistance to antiretroviral drugs. Those five patients who developed resistance were compliant to the treatment and they never had identifiable VL previous to syphilis infection.…”
Section: Discussionmentioning
confidence: 96%
“…Data analyzed by the Centers for Disease Control and Prevention (CDC) showed that 20% of syphilis cases among MSM were due to reinfections in Baltimore, USA, between 2010 and 2011 3 . A study conducted in Denmark has shown that 14.8% of the population with syphilis had more than one episode during a five-year period 19 . Similarly, in San Francisco, USA, between 2001 and 2002, 6.7% of the individuals already diagnosed with syphilis presented a new primary infection within one year 17 , and a review describing cases of syphilis in California, USA, between 2002 and 2006, reported a reinfection rate of 5.9% in MSM 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have identified several risk factors associated with an increased risk of BPH, including cardiovascular risk factors, a prior history of STDs (especially gonorrhoea), metabolic syndrome, chronic inflammation and sedentary activity [10,15,13,29,30]. HIV-infected men are at a higher risk of contracting STDs, which could be expected to translate into an increased risk of BPH [17,19,31]. Furthermore, HIV-infected individuals might be subject to chronic inflammation and accelerated ageing despite full viral suppression, and therefore at a higher risk of age-related diseases such as BPH [4,18,32,33].…”
Section: Discussionmentioning
confidence: 96%
“…Chronic inflammation (both systemic and local) [10][11][12], traditional cardiovascular risk factors [13,14] and prior sexually transmitted diseases (STDs) [15,16] have been found to be associated with BPH. Given the evidence that STDs and chronic inflammation are more prevalent in HIV-infected individuals [17][18][19], this population might also be subject to an increased risk of BPH. To our knowledge, no studies have previously estimated the risk of BPH in HIVinfected males compared with the background population.…”
Section: Introductionmentioning
confidence: 99%